Pengaruh Stres Kerja terhadap Produktivitas Kerja Karyawan pada Perseroan Terbatas (PT) Pucuk Jaya - Muhammad Akbar; Nuriyah Nuriyah; Hamidah Hamidah (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The purpose of this study was to determine the effect of work stress on employee work productivity at Pucuk Jaya Limited Liability Company (PT) Batu Engau District, Paser Regency. The research method used in this study is a quantitative research method. The population in this study were employees at PT. Pucuk Jaya Batu Engau District, Paser Regency, totaling 153 people. In this study, the sampling technique used was the proportionate stratified random sampling technique. The sample taken by the researcher was 25% x 153, the result was 38.25 rounded up to 38 respondents. The techniques used in calculating data analysis in this study were validity test, reliability test, simple linear regression test, correlation coefficient, determination coefficient, partial t test. The test results show that the work stress variable has an effect on employee work productivity, this is proven by the calculated t value of 8.507 with a significant value of 0.05>0.000 when compared to the t table value of 1.68830, then the calculated t> t table is (8.507>1.68830).